2009
DOI: 10.1111/j.1462-2920.2009.02035.x
|View full text |Cite
|
Sign up to set email alerts
|

A distinct population of Saccharomyces cerevisiae in New Zealand: evidence for local dispersal by insects and human‐aided global dispersal in oak barrels

Abstract: Humans have used S. cerevisiae to make alcoholic beverages for at least 5000 years and now this super-model research organism is central to advances in our biological understanding. Current models for S. cerevisiae suggest that its population comprises distinct domesticated and natural groups as well as mosaic strains, but we generally know little of the forces which shape its population structure. In order to test the roles that ecology and geography play in shaping the S. cerevisiae species we examined nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
218
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(235 citation statements)
references
References 38 publications
17
218
0
Order By: Relevance
“…For example, in a survey of 103 S. cerevisiae strains (surveyed at five loci), Diezmann and Dietrich (16) found that between 33 and 88% of human-associated isolates exhibited heterozygosity whereas none of the soil isolates they examined showed any evidence of heterozygosity. Human-associated environments might increase opportunities for outcrossing by bringing diverse strain backgrounds into proximity (17), by creating mass mating conditions (18), or by creating greater opportunities for spore dispersal by insect vectors (19). Alternatively, human-associated environments may have selectively favored genomically mixed strains.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a survey of 103 S. cerevisiae strains (surveyed at five loci), Diezmann and Dietrich (16) found that between 33 and 88% of human-associated isolates exhibited heterozygosity whereas none of the soil isolates they examined showed any evidence of heterozygosity. Human-associated environments might increase opportunities for outcrossing by bringing diverse strain backgrounds into proximity (17), by creating mass mating conditions (18), or by creating greater opportunities for spore dispersal by insect vectors (19). Alternatively, human-associated environments may have selectively favored genomically mixed strains.…”
Section: Resultsmentioning
confidence: 99%
“…Birds may play a defining role in long distance movement of microorganisms; for example, in the case of yeasts, it has been shown that insects may transport cells within approximately 10 km [9], while migratory birds are effective at longer distances [7]. So far, a few studies analyzed filamentous fungi associated with migratory birds [4,14], while bacteria and yeasts have been better investigated [4,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It must be noted that S. cerevisiae is not airborne, but requires a vector to move (23). Several studies show a flow of S. cerevisiae cells among wineries and natural environments (24), probably favored by animal vectors (25). In a recent paper, Francesca et al suggest the role of migratory birds as vectors of S. cerevisiae cells (26).…”
mentioning
confidence: 99%